Standardization of Gravity-Fed Low Head Drip Irrigation System under Variable Operational Head for Small Farms - Rigve, Rigve; Bhardwaj, Anil; Satpute, Sanjay; Singh, Jagmeet; Garg, Sunil (Indian Journal of Hill Farming, 2018)
A study was conducted to standardize the gravity fed low head drip irrigation system (LHDIS) under variable operational head of 3.0 m to 0.5 m. The results indicate that average emitter discharge as well as emission uniformity (EU) of the system increases withincrease in head, decrease in lateral length and decrease in number of laterals and viceversa. The average emitter discharge was observed to be maximum (3.76 l/h) under operating head of 3 m with 15 m length and 4 laterals and was minimum (0.31 l/h) when head decreased to 0.5 m and length and number of laterals increased to 30 m and 10 laterals, respectively. At 3 m and 2.5 m heads, 6 lateral lines each of 30 m length, 8 laterals each of 25 m length and 10 laterals of 20 m and 15 m length provide fair uniformity of water application through LHDIS with EU>70%. However, to obtain excellent uniformity (EU>90%) only 4 number of laterals each of 20 m or 15 m length can be used under theoperating head of 3 m. Also same number of laterals can be used at 2.5 m and 2.0 m heads when length of the lateral lines is reduced to 15 m, to obtain excellent uniformity. Keepingin view the practical difficulty in creating higher operating head (>3.0 m), one has to compromise between the EU of the system to be achieved and the size of the system in terms of the length and number of lateral lines to be used in the system.